The Influence of Online Games on Students’ Learning Motivation - Olivia Kristin Lumban Gaol; Vania Ailsa Nabilah; Lisbet Saulintia Sitanggang; Larissa Evelin Saragih; Cindy Leonysa V Lumban Toruan (Outline Publisher, 2026)
This research aims to determine the effect of online games on students’ learning motivation at Medan State University. The study employed a quantitative approach using survey methods with 32 respondents from the Faculty of Sports Science. Data were collected through Likert-scale questionnaires measuring online gaming intensity and learning motivation. The data were analyzed using descriptive statistics and simple linear regression. The results showed that online gaming has a significant negative effect on learning motivation. Students who spend more than three hours daily on online games tend to have lower motivation, decreased focus, and reduced academic discipline. Therefore, online gaming behavior must be controlled so that it remains recreational rather than disruptive to academic performance